EFFECT OF MATRIX CHANNEL GEOMETRY ON THE PERFORMANCE OF THE RECOVERY WHEEL - Abdulwahed Theeb, Maathe; Alawan Saleh, Fouad; Jaleel Mohamed, Duaa (Journal of Engineering and Sustainable Development, 2019)
In this study, effect of geometry channel of matrix on the performance of the recovery wheel was experimentally and numerically studied. Two channels geometry of matrix (rhombic and sinusoidal) made of aluminum with diameter (60 cm) and length (5, 10, and 15 cm) of wheel were used. A mathematical model for heat transfer between the air and matrix in recovery wheel is derived and solved numerically by using backward difference, fully explicit discretization in time finite difference method. Computer program was built in MATLAB to solve finite difference equations to find the effectiveness of the recovery wheel, and this model is validated with experimental work. The results showed that, the sensible effectiveness for rhombic and sinusoidal channels was increased with increasing wheel speed, also the increase of wheel thickness will increase the sensible effectiveness. When the wheel thickness increased from (5 to 15 cm), the effectiveness will be increase from (74. 39 to 81.48 %) for rhombic, and (79.16 to 85.89 %) for sinusoidal channel at speed (25 rpm). The sensible effectiveness for the sinusoidal channel is higher than the rhombic channel at any wheel speed and wheel thickness increase.